Valproate-related erythrodermia with reversible encephalopathy - Rener-Primec, Zvonka (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2014)
Cutaneous adverse reactions to antiepileptic drugs (AEDs) are usually easily recognized in daily clinical practice when they manifest as a morbilliform or maculopapular rash within the first few weeks after introducing an AED. Valproate (VPA)-induced encephalopathy is a rare but serious complication, presenting with impaired consciousness, with or without hyperammonemia, normal liver enzymes, and normal serum level of VPA. A 2-year-old Caucasian boy with severe developmental disability and pharmacoresistant epilepsy presented with fever, generalized erythrodermia, and encephalopathy, which resolved after discontinuation of valproate. Sodium valproate (30 mg/kg/day) was introduced 5 months previously, as the third drug in combination with vigabatrin and levetiracetam, due to frequent daily seizures. The clinical condition of generalized erythrodermia and encephalopathy was recognized by the treating physician as a possible adverse reaction to VPA: with the Naranjo scale it was probably associated with VPA (six points) and possibly associated with vigabatrin and levetiracetam (three and two points, respectively). After valproate withdrawal, the patient recovered completely. This case is of interest because erythrodermia was a clue to the recognition of valproate-related adverse reaction with severe central nervous system involvement without hyperammonemia and with normal liver enzymes - a very rare occurrence.
Keywords: adverse reaction; antiepileptic drugs; dermatologija; erythrodermia; reversible encephalopathy